Gonadotropin Stimulation Has Only a Limited Effect on the Concentration of Follicular Fluid Signalling Proteins: An Antibody Array Analysis - Bersinger, Nick A.; Eisenhut, Markus; Stute, Petra; von Wolff, Michael (International Journal of Reproductive Medicine, 2021)
Objective. The follicular fluid (FF) plays an essential role in the physiology of the follicle and the oocyte. Gonadotropin stimulation affects the FF steroid hormone and anti-Mullerian hormone (AMH) concentrations, which has been suggested to be the reason for lower oocyte competence in conventional gonadotropin stimulated in vitro fertilisation (cIVF) compared to natural cycle IVF (NC-IVF). To analyse the effect of gonadotropin stimulation on a broad spectrum of signalling proteins, we ran proteomic antibody arrays on FF of women undergoing both treatments NC-IVF and cIVF. Method. Twenty women underwent one NC-IVF and one cIVF treatment cycle. Follicular fluids of the first aspirated follicle were compared between the two groups using a protein microarray which included antibodies against 224 proteins related to cell signalling and reference proteins. Each of the 40 albumin-stripped, matched-pair samples was labelled in the reverse-dye (Cy3/Cy5) procedure before undergoing array hybridisation. Signal analysis was performed using normalisation algorithms in dedicated software. Five proteins yielding a value of P<0.05 in the array experiment (Cystatin A, Caspase-3, GAD65/67, ERK-1, and ERK-2) were then submitted to quantitative determination by ELISA in the same follicular fluids. Results. Array analysis yielded only a small number of differentially expressed signalling markers by unadjusted P values. Adjustment as a consequence of multiple determinations resulted in the absence of any significant differential marker expression on the array. Five unadjusted differentially expressed proteins were quantified immunometrically with antibodies from different sources. Follicular fluid concentrations of Cystatin A and MAP kinase ERK-1 concentrations were significantly higher in the cIVF than in the NC-IVF follicles, while GAD-2 (GAD65/67) did not differ. The assays for Caspase-3 and MAP kinase ERK-2 did not have the required sensitivities. Conclusion. In contrast to FF steroid hormones and AMH, FF concentrations of signalling proteins are not or only marginally altered by gonadotropin stimulation.